The Great Evangelical Disaster - Francis A. Schaeffer (UK Kingsway Publications, 1984)
Have Christians compromised their stand on truth and morality until there is almost nothing they will speak out against? Has the evangelical church itself sold out to the world? A provocative and challenging book-but one that is tempered by Dr. Schaeffer's deep commitment to Christ and love for the church.
Keywords: Spiritual Theology (3GddGghJ GdQhMjs; Theology